Teores pseudototais de cádmio, níquel, chumbo, cromo, cobre, bário e zinco em plantas de aveia e milho e em solo adubado com cama de aviário durante seis anos - Zanatta, Marizandra (2018)
Many studies are successful in using poultry litter as fertilizer, but because of the potentially toxic elements (EPTs) in their composition, with a tendency for surface accumulation, it may become a soil contaminant. The objective of this work was to quantify the pseudo-total contents of EPTs accumulated in the soil, as well as in oat plants and corn grains, after six consecutive poultry litter applications. The experiment was carried out in the experimental area of UTFPR / Pato Branco Campus in June 2011. The soil in the area is a typical dystrophic Red Latosol. The experimental design was a randomized complete block and four replications. The treatments consist of the annual application of increasing doses (0, 4, 8 and 12 Mg ha-1) of poultry litter, with moist base, always preceding the winter culture. The soil EPT content was quantified on the surface (0-5 cm) by the EPA 3051A method, after six years of treatments. The analytical determination of the pseudo-total contents of heavy metals in oat plants and corn kernels was obtained by nitro-per chloric digestion, the readings were performed by optical emission spectrometry with induced plasma (ICP-OES). The application of poultry litter promoted a linear increase in Zn and Ba contents, but the values are below the reference recommended by CONAMA. For Cd, Ni, Pb, Cr and Cu there was no effect of increasing doses of poultry litter. It is concluded that the soil under study does not present contamination by EPTs, despite the constant applications of poultry litter. In relation to oat plants, the application of poultry litter doses had no significant effect on Cu, Ni, Pb, Zn and Ba, however, it promoted a linear increase in Cr content. The levels of Cu, Ni, Zn and Cr in corn grains were not affected by increasing levels of poultry litter, however, the Cr content is above the maximum limit allowed for inorganic contaminants in food, although it has not been affected by aviary bed. Pb, Cd and Ba were not found in samples of corn grains.